An agent-based simulation model for energy saving in large passenger and cruise ships - Christos Bouras; Eirini Barri; Apostolos Gkamas; Nikos Karacapilidis; Dimitris Karadimas; Giorgos Kournetas; Yiannis Panaretou (CRC Press, 2021)
Undoubtedly, energy saving is of paramount importance in the shipping industry, as far as both the protection of environment and the reduction of the associated operating costs are concerned. In this direction, the International Maritime Organization aims to reduce ship emissions by at least 50% by 2050, while ships to be built by 2025 are expected to be a massive 30% more energy efficient than those built some years ago [IMO, 2018].